Semitelechelic HPMA Copolymers Functionalized with Triphenylphosphonium as Drug Carriers for Membrane Transduction and Mitochondrial Localization - Callahan, Jon (2006)
Semitelechelic HPMA (N-(2-hydroxypropyl)methacrylamide) copolymers possessing a single terminal lipophilic triphenylphosphonium (TPP) cation and fluorescent labels were synthesized to determine how the attached cation affected cellular uptake and intracellular trafficking. In vitro mitochondrial uptake fluorescence quenching assays using isolated mouse liver mitochondria indicated that only lower molecular weight (<5 kDa) BODIPY FL-labeled TPP-semitelechelic HPMA copolymers exhibited significant organelle localization or uptake. In vitro cellular uptake and intracellular trafficking was evaluated using cultured human ovarian carcinoma cells. Cells incubated with all types of TPP copolymers used in the study appeared to internalize the polymer by endocytosis only, and all of the internalized copolymer was confined to the lysosomal compartment after 24 h. Endocytotic uptake of the TPP–HPMA copolymer conjugates was rapid, suggesting that they were internalized by adsorptive endocytosis, rather than fluid-phase pinocytosis. Low-molecular weight (<5 kDa) and high-molecular weight (>5 kDa) semitelechelic copolymers, microinjected into cultured cells indicated that the TPP moiety did not significantly localize the polymers to mitochondria.